On the Etymology of the Witch: “Antimere” In the Tales (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This research thesis in children’s literature has as its theme an emblematic character of children’s tales: the witch. Nowadays, this supernatural character is omnipresent in children’s literature, and has been for several decades, as well as in the current wonderful universe, whether in cinema, through television series and cartoons, or even in novels. This character therefore appears in various works targeting all ages. It should also be noted that the globalization of the Halloween party has given rise in many countries to the development of witch costumes. However, this character to whom terrifying, repulsive and malicious characteristics and attributes have been attributed for generations has evolved a lot over the centuries.